Latin American Production on Gender Violence on Scopus, 2010 -2019 - M. Hernandez, Ronald; Saavedra-López, Miguel; Calle-Ramirez, Xiomara; Cjuno, Julio; Escobedo, Fernando (International Journal of Criminology and Sociology, 2022)
The study describes the characteristics of publications on gender violence written by authors affiliated with Latin American institutions, in journals indexed to Scopus during the period 2010-2019. A descriptive and retrospective analysis of 2,568 articles is carried out. Latin American scientific production represents 5.3% of world production. Brazil is the country with the highest production, followed by Mexico and Chile. Latin American scientific production has been published in 572 journals. Ciencia e Saude Coletiva (Brazil) is the journal with the largest number of publications, followed by Cadernos de Saude Publica (Brazil) and Journal of Interpersonal Violence (United States). besides, the authors are mainly affiliated with the Universidade de Sao Paulo - USP, followed by the Fundacao Oswaldo Cruz Universidade Federal do Rio Grande do Sul. Finally, the keywords, domestic violence, intimate partner violence and gender violence present an increasing trend of studies since 2016. Therefore, it is necessary to strengthen and stimulate the generation and dissemination of scientific studies by Latin American researchers.